Creative Writing Club(Sistem Swa-Mandiri Pelatihan Menulis - Kusnawan, Aep (Jurnal Ilmu Dakwah, 2009)
CWC (Creative Writing Club) constitutes a system that is formatted to fit-up the human resource with such character as creative, dynamic, ikhlash, forward oriented and futuristic. It constitutes idea in order to push its amends writing culture, that seemingly is now still far its appeal of oral-culture. With CWC is expected emerges consciousness to write at circle educator; fitting-up self-potency via agglomerate container that brought off as self-independent, that itâs out-put can fill each newspaper, magazine, tabloid, bulletin, even binds books by educators,Â  that quality and also its writing amount getting days getting increases.